Implementasi Good Corporate Governance Pada Bidang Perindustrian Ditinjau Dari Perspektif Islam - Asvianty, Mia Ade; Laksono, Mukhammad Kharis Wildan; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
Lately, good corporate governance is often discussed by the public and has become a hot topic among the business world. In general, Good Corporate Governance has 5 basic principles that must be carried out according to applicable standards. From these principles, if implemented properly, it can increase added value for shareholders and for the company to get a good and positive image in society and the public. The purpose of this research is to explain and describe or describe broadly the implementation of good corporate governance based on studies from an Islamic perspective based on several values that must be carried out in companies. The subject of this research is a company engaged in the furniture industry with a 100% percentage of shares owned by the founding family because this company is a family furniture industry company that is run or managed by the family members themselves.